STRES BERKENDARA AKIBAT KEMACETAN LALU LINTAS DAN PERILAKU AGRESIF BERKENDARA - Muhammad Iqramullah; Asmulyani Asri; Nurfitriany Fakhri (Poltekkes Kemenkes Surabaya, 2022)
Traffic jams that occur on the highway becomes an obstacle and problems for motorists who are driving and cause drivers to behave aggressively. The purpose of this study was to determine the relationship between driving stress caused by traffic jams and aggressive driving. The subjects in this study amounted to 143 students of the Faculty of Psychology, State University of Makassar in the second to eighth semesters who drive a motorized vehicle every day when they go to campus. The sampling technique in this research is accidental sampling, which is a non-probability sampling technique. The method used in this study is a quantitative method by using a traffic jam questionnaire and measuring a driving stress scale and an aggressive driving scale. The data analysis technique used in this research is Spearman Rho. Based on the results of data analysis, it was found that there was a significant positive relationship between driving stress due to traffic jams and aggressive driving. The higher the stress of driving due to traffic jams, the higher the aggressive driving. The results of the study can be used by the government as a reference in formulating programs and policies regarding the importance of mental health in driving, as well as for further researchers to develop this research using different and more varied demographic variables.